Variability and genetic merits of white Guinea yam landraces in Nigeria - Agre, Paterne A.; Edemodu, Alex; Obidiegwu, Jude E.; Adebola, Patrick; Asiedu, Robert; Asfaw, Asrat (Frontiers in Plant Science, 2023)
Landraces represent a significant gene pool of African cultivated white Guinea yam diversity. They could, therefore, serve as a potential donor of important traits such as resilience to stresses as well as food quality attributes that may be useful in modern yam breeding. This study assessed the pattern of genetic variability, quantitative trait loci (QTLs), alleles, and genetic merits of landraces, which could be exploited in breeding for more sustainable yam production in Africa. A total of 86 white Guinea yam landraces representing the popular landraces in Nigeria alongside 16 elite clones were used for this study. The yam landraces were genotyped using 4,819 DArTseq SNP markers and profiled using key productivity and food quality traits. Genetic population structure through admixture and hierarchical clustering methods revealed the presence of three major genetic groups. Genome-wide association scan identified thirteen SNP markers associated with five key traits, suggesting that landraces constitute a source of valuable genes for productivity and food quality traits. Further dissection of their genetic merits in yam breeding using the Genomic Prediction of Cross Performance (GPCP) allowed identifying several landraces with high crossing merit for multiple traits. Thirteen landraces were identified as potential genitors to develop segregating progenies to improve multiple traits simultaneously for desired gains in yam breeding. Results of this study provide valuable insights into the patterns and the merits of local genetic diversity which can be utilized for identifying desirable genes and alleles of interest in yam breeding for Africa.